Chapter Learning and Teaching in Higher Education in Post-Covid Times: A Digital Transformation - Schmidt-Lauff, Sabine (Studies on Adult Learning and Education, 2023)
Learning and teaching in higher education can help to face the rapidly changing demands and transformations in social, professional, and individual life. «Digitalisation is not only an additional challenge but also an effective means to address key challenges for higher education in the 21st century» (Rampelt et al. 2019, 6). Digital practices in Higher Education forced by the Covid-19 disruption are challenging educational processes at every level. Digitization is here no longer just about the question of the technical dimension, but, about the structural interweaving and relational co-constitution of the digital with the social, the cultural, and the individual. Here the INTALL@home vision of learning international comparison without being physically mobile - theoretically framed and elaborated in this paper - starts.